EFFECT OF FRAUD DIAMOND ON FRAUD FINANCIAL STATEMENT DETECTION WITH AUDIT COMMITTEE AS MODERATION VARIABLES IN MANUFACTURING COMPANIES LISTED IN INDONESIA STOCK EXCHANGE IN THE PERIOD OF 2015-2017 - Wailanan, Evi Juita (International Journal of Public Budgeting, Accounting and Finance, 2019)
This study aims to determine the effect of Financial Stability, External Pressure, Financial Targets, Personal Financial Needs, Industrial Conditions, Monitoring Ineffectiveness, Auditor Change, Board of Directors Change to Fraud Financial Statement Detection with Audit Committee as Moderating variables in Companies listed on the Indonesia Stock Exchange Period 2015-2017. The population in this study amounted to 160 companies. The sampling method uses purposive sampling and the number of observation samples is 60 companies. This type of research is descriptive quantitative by testing classical assumptions and Multiple Regression Analysis (MRA) tests using two regression equations. The results of testing the data show that simultaneously and partially all independent variables have no effect on Fraud's Financial Statement Detection. The second equation shows all the independent variables have a significant effect on Fraud's Financial Statement Detection. Partially Financial Stability and Financial Stability Interaction affect Fraud's Financial Statement Detection. Whereas External Pressure, Financial Targets, Industrial Conditions, Monitoring Ineffectiveness, Auditor Change, Board of Directors Change, Interaction of External Pressure, Interaction of Financial Target, Interaction of Industrial Conditions, Interaction of Monitoring Ineffectiveness, Interaction of Auditor Change and Interaction of Directors Change did not affect Fraud's Financial Statement Detection.